Analisis Metode Split Tensile Test Komposit Laminat Hybrid Jute E-Glass Akibat Beban Tarik Beton Kolom Silinder - Tambusay, M. Ibnu; Zulfikar, Achmad Jusuf; Iswandi, Iswandi (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
In this study, reinforcement of the concrete structure was done by coating it with a laminate composite material from a combination of reinforcement from natural materials (woven jute cloth sheets) and synthetic materials (woven e-glass fiber sheets). The purpose of this study was to determine the split tensile strength of cylindrical column concrete (BKS) using the split tensile test method due to the application of e-glass laminate hybrid composite sheath (KLHJG), to analyze the validity of the data using the normally distributed data method (DTN). on the results of the shear strength test of the KLHJG sheath as reinforcement for BKS, and analysis of the effect of applying KLHJG's sheath on the tensile strength of BKS. Specimens were printed based on the ASTM C496 test standard by immersion in clean water for 28 days and drying in the open air for 28 days. The KLHJG variation consists of JGJ, JJG, JJJG, JGJG, and GJGJ. Each variation consists of 3 repetitions of the test. The process of providing KLHJG casings to BKS uses the Vacuum Bagging method. Data validity uses the probability density function method. The results of the study show that the provision of KLHJG can increase the split tensile strength by up to 800%. Thus, the KLHJG application has the potential to be applied as a BKS booster.